Influence of Seasons and Extenders on Quality and Freezability of Gir Bull Semen under Middle Gujarat Climate - Chaudhari, DV; Patel, JA; Hadiya, KK; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was conducted to evaluate the seasonal influence (peak winter and summer) and the efficacy of three extenders (egg yolk based TFYG extender and egg yolk free soya bean based commercial extenders Optixcell and Andromed) on quality and freezability of Gir bull semen in Middle Gujarat. Semen ejaculates (6/bull/season, total 36) revealed mean ejaculate volume 6.49±0.30 ml, sperm concentration 1212.36±58.10 million/ml, progressive motility 74.17±0.78 %, live sperm 81.39±0.80 %, abnormal sperm 7.36±0.31 %, and sperm with intact plasma membrane 81.31±0.98 % and intact acrosome 94.81±0.24 %. Only the progressive sperm motility was significantly (P<0.05) higher (76.39±0.97 % vs. 71.94±1.00 %) with lesser sperm abnormality (6.17±0.37 % vs. 8.56±0.30 %) during winter than in summer. Semen samples split diluted with TFYG, Optixcell and Andromed extenders recorded the overall mean values of progressive sperm motility, livability, abnormality, plasma membrane integrity and acrosomal integrity during winter season as 77.87±0.51, 77.50±0.45, 5.56±0.20, 76.02±0.81 and 94.35±0.29 on dilution; 72.41±0.51, 70.50±0.64, 5.96±0.26, 71.20±0.79 and 93.09±0.32 at pre-freeze stage; 41.30 ±0.94, 50.28±1.03, 9.15±0.31, 29.89±0.40 and 90.65±0.40 at post-thaw stage, respectively. The respective values in summer season were 72.13±0.60, 75.50±0.60, 7.48±0.25, 75.61 ±0.55 and 94.09±0.30 on dilution; 65.46±0.66, 69.41±1.05, 8.89±0.28, 69.70±0.66 and 92.63 ±0.33 at pre-freeze stage; 31.48±0.52, 45.09±0.85, 13.48±0.33, 26.85±0.71 and 91.26±0.38 at post-thaw stage. The overall mean sperm post-thaw motility/longevity at 0, 30, 60 and 120 min of incubation at 37°C was 41.20±1.51, 35.19±1.47, 28.80±1.75 and 17.50±1.47 % during winter season and 31.57±0.89, 26.20±0.77, 20.37±0.83 and 13.80±0.77% in summer season, respectively. The initial quality as well as freezability of semen in terms of motile, live, normal and HOS reactive sperm including post thaw longevity were better in winter season than in summer season. Further, the values of all the five semen quality parameters studied were comparatively better in Optixcell than TFYG and Andromed extenders with significant differences only in sperm progressive motility in both the seasons. The season x extender interaction was not significant for any of the sperm quality parameters studied.